Features of the processes of heat and mass transfer when drying a large thickness layer of wood biomass. (May 2021) - Kuznetsov, G.V.; Syrodoy, S.V.; Nigay, N.A.; Maksimov, V.I.; Gutareva, N.Yu.
Abstract: The article presents the results of the experimental studies of heat transfer in a layer of moist wood biomass under conditions of its dehydration when heated in a high-temperature gas environment. The basic laws of the formation process of the temperature field of the biomass layer during its dehydration have been established. It is shown that essentially nonuniform temperature fields are formed in the wood biomass layer, the form of which is a consequence of the influence of a complex of heat and mass transfer processes occurring together under conditions of heat conduction, intense phase transformations (evaporation and condensation of water), and water vapor diffusion through the porous frame of the biomass layer. It has also been found that as a result of intense absorption of heat during evaporation of moisture and vapor filtration, local cooling of biomass occurs. A physical model of heat and mass transfer processes in the porous structure of moist wood biomass upon heating has been formulated, which differs from the well-known detailed descriptions of the processes of filtering water vapor into the area of the relatively low temperatures from the zone of intense evaporation, condensation and subsequent secondary evaporation. Graphical abstract: Image 1 Highlights: A new physical mechanism for drying large layers of biomass has been established. When drying wood in the biomass layer formed steam, moving in different directions. Water vapor can condense in the biomass layer, causing the temperature to rise. During drying, inhomogeneous temperature fields are formed in the biomass layer. Formulated a model that describes the mechanism for removing moisture from the biomass.